PERANCANGAN SISTEM INFORMASI PENGECEKAN ASET BERGERAK DI DINAS PEMADAM KEBAKARAN DAN PENYELAMATAN KABUPATEN BANYUWANGI - Hilmiatus Soleha; Firman Santoso; Salam Bikwanto (CV. Denasya Smart Publisher, 2025)
This research aims to design and develop a web-based information system for the Fire and Rescue Department of Banyuwangi Regency to enhance the effectiveness of the mobile asset checking process. Currently, the process of checking assets such as operational vehicles and fire-fighting equipment is still done manually using printed forms. This manual method causes many issues, including data loss, inaccurate reports, and inconsistencies due to human factors. To overcome these problems, an information system was designed using a systematic waterfall method, starting from requirements analysis and system design with Unified Modeling Language (UML), to the implementation and testing phases. The designed system allows field officers (teams) to digitally report the condition of assets via mobile devices or computers. These reports are then validated by the section head before being forwarded to the head of the department for approval. Thus, this system is expected to be an effective solution to support the operational efficiency of the Banyuwangi Regency Fire and Rescue Department.